KETERLAKSANAAN KURIKULUM 2013 PADA MATA PELAJARAN PENJASORKES DI SEKOLAH MENENGAH ATAS NEGERI SE-KOTA SINGKAWANG - Wahyudi, Wahyudi; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is the lack of information about how the 2013 curriculum was implemented by the teacher so that the material received by students is not optimal because students who only memorize concepts, record what the teacher is lecturing, passively, and rarely use initial knowledge as a basis for learning planning . The purpose of this study was to determine the Implementation Process of Physical Education Learning with 2013 Curriculum in Singkawang City High Schools in 2018/2019 Academic Year.The research method used was quantitative descriptive research in the form of a survey. This research was conducted in April 2019. And the sample was 225 students of class X in Singkawang City. taken using simple random sampling technique. Data collection techniques by distributing questionnaires to state high schools in Singkawang City.the results of this study were obtained Physical Education Learning Physical Education With Curriculum 2013 In Singkawang City High Schools in Academic Year 2018/2019 in the good category at 24.9%, in the sufficient category at 61.3% and the unfavorable category at 8.9% and at bad category 4.9%. These results can be concluded that the implementation of Penjasorkes Learning with the 2013 curriculum in Singkawang City High Schools is sufficient.Â Keywords : Implementation, 2013 Curriculum, Penjasorkes